2010
DOI: 10.1590/s0102-09352010000500033
|View full text |Cite
|
Sign up to set email alerts
|

Ostrich (Struthio camelus) gastric diseases in Minas Gerais, Brazil, from 1997 to 2009

Abstract: Communication [Comunicação]Ostrich (Struthio camelus) gastric diseases in Minas Gerais, Brazil, from 1997 to 2009 (Doenças gástricas de avestruzes em Minas Gerais)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
1
3
0
2
Order By: Relevance
“…This observation is particularly true for ostriches raised in such environments as noticed in the farm visited in the second case and as reported by other authors (Komnenou et al, 2003;Long et al, 2009). The post mortem findings in the two dead cases were identical to those reported by Mendonça et al (2010) and Nagarajan et al (2011) in cases of proventriculus and ventricular inpaction in ostriches. Proventricular and ventricular impaction is the commonest health problem and the most life-threatening clinical condition in ostriches, especially young ones (Stomach, 1992).…”
Section: Discussionsupporting
confidence: 86%
“…This observation is particularly true for ostriches raised in such environments as noticed in the farm visited in the second case and as reported by other authors (Komnenou et al, 2003;Long et al, 2009). The post mortem findings in the two dead cases were identical to those reported by Mendonça et al (2010) and Nagarajan et al (2011) in cases of proventriculus and ventricular inpaction in ostriches. Proventricular and ventricular impaction is the commonest health problem and the most life-threatening clinical condition in ostriches, especially young ones (Stomach, 1992).…”
Section: Discussionsupporting
confidence: 86%
“…Bu raporda sunduğumuz gibi benzer sindirim problemleri ile karşılaşılmaması açısından pikanın kontrol edilmesi önemlidir. Deve kuşu çiftliklerinde sindirim sistemi hastalıkları sıklıkla görülmekte ve ekonomik kayıplara neden olabilmektedir (5,13,14). Sindirim sisteminde yabancı cisimlerin varlığı genellikle anamnez, klinik bulgular, laboratuvar testleri ve radyolojik bulgulara göre teşhis edilmektedir (4,8,11).…”
Section: Klinik Tanıunclassified
“…Endoparasites in GIT can block the flow of ingested feed and result in impaction (Shanawany and Dingle, 1999;Cooper, 2005;Mendonça et al, 2010;Nemejc and Lukesova, 2012). Some parasites may even perforate the GIT; for example, Libyostrongylus douglassii resides in the gastric layers of ostriches (Sánchez-Ayala et al, 2018) and heavy infestation of this parasite obstructs feed passage, especially in young chicks (Shanawany and Dingle, 1999).…”
Section: Feed Contamination and Other Predisposing Biotic Factorsmentioning
confidence: 99%
“…Similar findings were reported from Brazil, showing that 46% of diagnosed dysfunctions in ostriches were gastroenteric diseases. Among the GIT conditions, 83% were gastric impactions and 17% were infectious (caused by bacteria) or parasitic gastritis caused by the nematode Libyostrongylus douglassii (Mendonça et al, 2010). Another retrospective study spanning 40 years from a French wildlife sanctuary reported that impaction accounted for 30 -35% of all mortalities in ostriches (Lamglait, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation